Whiteboard Smart Wipe with Ethanol Spray using Linear Rod and DC Gearmotor - Mohd Khalil Fisal, Muhammad Idham; Sha'abani, Mohd Nurul Al Hafiz (Multidisciplinary Applied Research and Innovation, 2024)
In modern and professional environments, maintaining clean whiteboard surfaces is essential but often challenging and time-consuming. This project addresses this issue by developing an automated whiteboard cleaning system that combines mechanical structure, electrical components, and ethanol spray features. The primary objective is to design and implement a mechatronic system driven by a lead rod coupled with DC gearmotor and controlled by an Arduino Uno microcontroller to facilitate the systematic cleaning of whiteboards. Additionally, an ethanol spray system powered by DC water pump is integrated to efficiently remove stubborn ink. The system’s effectiveness was validated through simulations and practical tests, demonstrating its ability to clean whiteboards thoroughly and automatically. The results indicate that the system is user–friendly for all consumers. Almost 70% of the whiteboard ink has been efficiently removed. In conclusion, this project provide solution for maintaining whiteboard cleanliness in shared space.